2021
DOI: 10.3389/feduc.2021.629213
|View full text |Cite
|
Sign up to set email alerts
|

How Personality Traits Are Related to the Attitudes Toward Forced Remote Learning During COVID-19: Predictive Analysis Using Generalized Additive Modeling

Abstract: BackgroundDuring the COVID-19 pandemic, universities all over the world have had to reorganize their work for remote education to ensure continuity of learning. This situation has forced both teachers and students into an atypical, very specific situation, in which they need to cope with a number of psychological factors. Meanwhile, there is a research gap in academic knowledge of the social and psychological factors that determine attitudes toward forced remote learning.ObjectiveTo analyze the psychological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Previous research reported mixed results regarding the impact of gender and age on digital learning (e.g., González-Gómez et al, 2012 ; Lai and Hong, 2015 ; Ramírez-Correa et al, 2015 ; Adams et al, 2018 ). In the context of the COVID-19 pandemic, gender did not show an effect regarding the attitude to remote learning ( Dikaya et al, 2021 ). In the present study, gender and study stage (bachelor versus master program) did not play a significant role, but age did.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported mixed results regarding the impact of gender and age on digital learning (e.g., González-Gómez et al, 2012 ; Lai and Hong, 2015 ; Ramírez-Correa et al, 2015 ; Adams et al, 2018 ). In the context of the COVID-19 pandemic, gender did not show an effect regarding the attitude to remote learning ( Dikaya et al, 2021 ). In the present study, gender and study stage (bachelor versus master program) did not play a significant role, but age did.…”
Section: Discussionmentioning
confidence: 99%
“…Student engagement and adaptability were also found to significantly correlate with academic emotion (Zhang et al, 2021). An analysis carried out at a university in Russia (Dikaya et al, 2021) revealed an association between students' attitudes to forced remote learning and their interpersonal communicative skills and thinking and learning styles. A survey of students' emotions during and perceptions of the shift to online teaching at a Greek university (Karalis and Raikou, 2020) found that although the majority of the students were satisfied with the new way of attending classes, upon the closure of the university over three quarters had felt negative emotions such as stress and anxiety about how the studies would be completed, fear of the possibility of non-continuation of studies, and/or sadness about the interruption; after the online classes had started, some of the initial negative emotions gave way to an increase in relief that the semester would not be lost, and joy at the continuity of the classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in online classrooms, students have increased autonomy over their participation (e.g., through a chat board). Due to reduced social pressures, shy students may feel more comfortable contributing in class online and may be more motivated to learn (Dikaya et al, 2021). For the same reasons, students high in avoidance may not be less test anxious in online learning environments.…”
Section: Limitations and Future Researchmentioning
confidence: 99%